Developing an atlas based on frond venation patterns analysis of polypodiales in Tarakan - Fadhlan Muchlas Abrori; Aidil Adhani (JPBI (Jurnal Pendidikan Biologi Indonesia), 2017)
This study aims to identify and analysis of frond venation pattern of Polypodiales in Tarakan, which then developing an atlas based on the results obtained. The results of identify and analysis the frond venation pattern of Polypodiales showed that there were 14 species of Polypodiales. The venation pattern found in Polypodiales were  reticulate and open forked. While in the development of an atlas, the assessment result of the content feasibility aspect by the content expert obtained 90.77% (valid), and assessment result of the presentation feasibility aspect obtained 100% (valid). The assessment result of the book size aspect by the media expert obtained 90% (valid), while assessment result of the book cover design aspect obtained 93.33% (valid), and assessment result of the content book design obtained 91.42% (valid). The assessment result of the language usage by language expert obtain 92% (valid), and assessment result of the language accuracy obtained 96% (valid). The field assessment result by lecturer for the easiness aspect obtained 92.31% (valid), the attractiveness aspect obtained 100% (valid), and the understandable aspect obtained 90% (valid). Meanwhile, the field assessment result by student for the easiness aspect obtained 97.43% (valid), the attractiveness aspect obtained 93.33% (valid), and the understandable aspect obtained 100% (valid).